Signatures of the disjoint union box product of some proper autographs - Egarguin, Neil Jerome A. (UP Los Baños Journal, 2015)
A proper autograph is graph whose vertices can be labeled by a set S of positive integers, called a signature, in such a way that vertices are adjacent if and only if the absolute difference of their labels is in S. The disjoint union and box product of some proper autographs are taken and signatures are derived.